The Pittsburgh Lung Screening Study (PLuSS): Outcomes within 3 Years of a First Computed Tomography Scan - Wilson, David O. (American Thoracic Society, 2008)
Rationale: The role of computed tomography (CT) screening for lung cancer is controversial, currently under study, and not yet fully elucidated. Objectives: To report findings from initial and 1-year repeat screening low-radiation-dose CT of the chest and 3-year outcomes for 50- to 79-year-old current and ex-smokers in the Pittsburgh Lung Screening Study (PLuSS). Methods: Notified of findings on screening CT, subjects received diagnostic advice from both study and personal physicians. Tracking subjects for up to three years since initial screening, we obtained medical records to document diagnostic procedures, lung cancer diagnoses, and deaths. Measurements and Main Results: 3,642 and 3,423 subjects had initial and repeat screening. A total of 1,477 (40.6% of 3,624) were told about noncalcified lung nodules on the initial screening and, before repeat screening, 821 (55.6% of 1,477, 22.5% of 3,642) obtained one or more subsequent diagnostic imaging studies (CT, positron emission tomography [PET], or PET-CT). Tracking identified 80 subjects with lung cancer, including 53 subjects with tumor seen at initial screening. In all, 36 subjects (1.0% of the 3,642 screened), referred for abnormalities on either the initial or repeat screening, had a major thoracic surgical procedure (thoracotomy, video-assisted thoracoscopic surgery [VATS], median sternotomy, or mediastinoscopy) leading to a noncancer final diagnosis. Out of 82 subjects with thoracotomy or VATS to exclude malignancy in a lung nodule, 28 (34.1%) received a noncancer final diagnosis. Forty of 69 (58%) subjects with non–small cell lung cancer had stage I disease at diagnosis. Conclusions: Though leading to the discovery of early stage lung cancer, CT screening also led to many diagnostic follow-up procedures, including major thoracic surgical procedures with noncancer outcomes.